Parainfluenza virus infections in a tropical city: clinical and epidemiological aspects - Fé,Mariana Mota Moura (2008)
Little information on the epidemiology and clinical characteristics of human parainfluenza virus (HPIV) infections, especially in children from tropical countries, has been published. The aim of this study was to determine the frequency of HPIV infections in children attended at a large hospital in Fortaleza in Northeast Brazil, and describe seasonal patterns, clinical and epidemiological characteristics of these infections. From January 2001 to December 2006, a total of 3070 nasopharyngeal aspirates collected from children were screened by indirect immunofluorescence for human parainfluenza viruses 1, 2, and 3 (HPIV-1, 2 and 3) and other respiratory viruses. Viral antigens were identified in 933 samples and HPIV in 117. The frequency of HPIV-3, HPIV-1 and HPIV-2 was of 83.76%, 11.96% and 4.27%, respectively. Only HPIV-3 showed a seasonal occurrence, with most cases observed from September to November, and with an inverse relationship to the rainy season. Most HPIV-3 infections seen in outpatients were diagnosed as upper respiratory tract infections.